The trends of socioeconomic inequities in full vaccination coverage among children aged 12-23 months from 2000 to 2017: evidence for mitigating disparities in vaccination service in Zhejiang province - Yu Hu; Yaping Chen; Ying Wang; Hu Liang; Huakun Lv (Taylor & Francis Group, 2021)
Objective This study aimed to evaluate the trends and changes in inequities in the completeness of the primary vaccination (CPV) scheduled before the first year of age among children aged 12-23 months, from 2000 to 2017. Methods: Data were extracted from five rounds of the provincial vaccination coverage survey (PVCS) in 2000, 2004, 2008, 2014 and 2017, respectively. The household income per month was used as an index of socioeconomic status for the inequity analysis. The concentration index (CI) was used to quantify the degree of inequity, and the decomposition approach was applied to quantify the contributions from independent factors to inequity in the CPV. Results: The CPV was significantly improved from 2000 to 2017, with 67.0% for the 2000 PVCS and 86.0% for the 2017 PCVS. The CI value decreased from 0.29839 for the 2000 round to 0.03601 for the 2017 round. The decomposition analysis indicated that independent variables such as birth order, ethnic group, mother's education, maternal employment status, residence, immigration status and the percentage of the total health spending allocated to public health could explain the inequity in the CPV in varying degrees. Conclusions: A sharp reduction in socioeconomic inequity in the CPV was observed from 2000 to 2017. Policy recommendations to reduce the inequality in the CPV should focus on children with the risk factors found in this study, for better outcome in full vaccination and long-lasting herd immunity.